PRODUCTIVITY AS INTEGRAL INDICATOR OF EFFICIENCY OF APPLYING OF NANOMETALS IN SOYBEAN GROWING TECHNOLOGY - Новицька, Н. В.; Пилипчук, М. Ю.; Ситар, О. В. (Scientific Progress & Innovations, 2013)
The results of studies of soybean yield on black soils typical steppe of Ukraine, depending on the method of application and concentration of the solution of complex multi-component nanoparticles of metals were highlighted. It is established that the technology of soybean growing the seed treatment before planting by nanometal solution at a concentration of 240 mg/L and addition a spraying of crops in the budding stage is effective. Using nanometal for pre-treatment of soybean seeds in a concentration of 240 mg/L with the normal spend of 0,1l /ha of seeds and additional spraying of crops with a solution at a concentration of 240 mg/L in the budding stage against the backdrop of mineral fertilizers in normal N60P60K60 provides the increasing of crop yield by 1,5-2,5%.